PENERAPAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA : SYSTEMATIC LITERATURE - Mitrayana Mitrayana; Dadang Juandi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
Problem-based learning (PBL) is one of the learning models used in learning mathematics. The purpose of this study was to analyze the impact of implementing problem based learning in learning mathematics at the elementary, junior high, high school and university levels. The method used is a Systematic Literature Review (SLR) for all articles indexed in Google Scholar, ERIC and Scoopus published from 2014 to 2022. The research instrument guidelines used the PRISMA protocol adjusted to the inclusion criteria. The moderator variables involved in this study were the year of publication, education level, research class, research methods, research instruments and data analysis used. All data obtained is presented in a quantitative descriptive manner. The results of the SLR research show that research on the application of problem-based learning in mathematics learning has received good attention, especially in 2019. This research was predominantly carried out at the junior high school level in class VIII. The study is dominated by quantitative research methods with more than one research instrument. The majority of studies use research data analysis which uses descriptive analysis